Numerical Study of Fluid Dynamics in Suspension Culture of iPS Cells - Masaki Yano; Takuya Yamamoto; Yasunori Okano; Toshiyuki Kanamori; Mashiro Kino (ASEAN Journal of Chemical Engineering, 2017)
In a suspension culture of iPS cells, the shear stress generated during mixing is expected to promote differentiation of induced pluripotent stem (iPS) cells. The stress on the cells can be controlled by rotational rate and shape of impeller. However, it is difficult to optimize these operative parameters by experiments. Therefore, we have developed a numerical model to obtain the average and the maximum shear stress in two kinds of stirred tanks and an orbital shaking cylindrical container. The present results showed that the shear stress strongly depended on the type of mixing and lesser extent on the shape of the impeller. The average shear stress is larger in the shaking mode than that in the stirring mode. In contrast, the maximum shear stress is much smaller in the shaking than the stirring. These results suggest that stirring and shaking should be selectively used depending on the application